2008
DOI: 10.1021/jm800295d
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of 2-(1H-Indazol-4-yl)-6-(4-methanesulfonyl-piperazin-1-ylmethyl)-4-morpholin-4-yl-thieno[3,2-d]pyrimidine (GDC-0941) as a Potent, Selective, Orally Bioavailable Inhibitor of Class I PI3 Kinase for the Treatment of Cancer

Abstract: Phosphatidylinositol-3-kinase (PI3K) is an important target in cancer due to the deregulation of the PI3K/ Akt signaling pathway in a wide variety of tumors. A series of thieno[3,2-d]pyrimidine derivatives were prepared and evaluated as inhibitors of PI3 kinase p110alpha. The synthesis, biological activity, and further profiling of these compounds are described. This work resulted in the discovery of 17, GDC-0941, which is a potent, selective, orally bioavailable inhibitor of PI3K and is currently being evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
537
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 702 publications
(577 citation statements)
references
References 30 publications
26
537
0
Order By: Relevance
“…To establish whether increased MAPK activity is causative for the loss of ISCs and crypts, we inhibited the downstream MEK1/2 kinases using AZD6244 36 and alternatively the phosphatidylinositol 3 kinase cascade using the specific inhibitor GDC0941. 37 Significantly, MEK inhibition by AZD6244 had a similar protective effect as PLX4720 and supported organoid survival in the presence of doxycycline (Figure 5d). In contrast, inhibition of the phosphatidylinositol 3 kinase cascade by GDC0941 did not rescue organoid survival.…”
Section: Above)mentioning
confidence: 67%
“…To establish whether increased MAPK activity is causative for the loss of ISCs and crypts, we inhibited the downstream MEK1/2 kinases using AZD6244 36 and alternatively the phosphatidylinositol 3 kinase cascade using the specific inhibitor GDC0941. 37 Significantly, MEK inhibition by AZD6244 had a similar protective effect as PLX4720 and supported organoid survival in the presence of doxycycline (Figure 5d). In contrast, inhibition of the phosphatidylinositol 3 kinase cascade by GDC0941 did not rescue organoid survival.…”
Section: Above)mentioning
confidence: 67%
“…Thus, intermediate aldehydes 7 23 and 10 24 that are not commercially available were prepared and donated by GSK. The project provides a showcase for two mechanistically important reactions frequently employed in the pharmaceutical industry: reductive amination 25 and the Suzuki-Miyaura reaction 26 for biaryl coupling.…”
Section: Target Compound Synthesis and Screening Resultsmentioning
confidence: 99%
“…The project provides a showcase for two mechanistically important reactions frequently employed in the pharmaceutical industry: reductive amination 25 and the Suzuki-Miyaura reaction 26 for biaryl coupling. Preliminary investigations of the chemistry by GSK following the procedures described by Folkes et al 23 revealed some problems. Consequently, in order to give the best chance for many analogues to be completed, the students are provided with modified reaction procedures, and are not encouraged to vary them.…”
Section: Target Compound Synthesis and Screening Resultsmentioning
confidence: 99%
See 2 more Smart Citations